Obtaining sorbents based on natural mineral raw materials - Shachneva, Evgeniya Yu. (Journal of the Belarusian State University. Ecology, 2022)
The presented material shows the results of studies of sorbents obtained on the basis of natural mineral raw materials -the flask of the Astrakhan region. The role of technogenic impact on the process of environmental pollution is shown. The methods of obtaining new sorption materials based on natural formations, the main component of which is flask, which is a sedimentary siliceous rock, are considered. The structure of this natural mineral is described, consisting of 90 % fine-grained amorphous aqueous silica with admixtures of clay matter, carbonates, silicon organic residues, quartz, feldspar, volcanic glass, etc. The studied component is close to trepel in its chemical and mineral composition, differing from it in greater density. The main adsorption-structural and physico-chemical characteristics of the sorbents under consideration are investigated. The values of the physicochemical parameters of the obtained materials, such as the porosity of the sorbent for acetone, the total pore volume of the sorbent for water, the moisture content in the sorbent and the pH of the aqueous suspension of the sorbent, are calculated. Their adsorption-structural characteristics, such as the specific surface area of the sorbent and bulk density, are determined. The presented material describes the nature of the surface and the structure of the flask as a natural mineral raw material underlying the methods of obtaining the sorbents in question. This suggests possible sorption properties of the described products. Graphical diagrams of the structure of clay minerals as layered crystal structures are presented, the atomic lattice of the substance of which combines two main structural elements. A graphical diagram of the described structural elements is presented. In the course of the work, the scheme of the graphic representation of the montmorillonite structure is considered, and the mineral and chemical composition of the flask of the Astrakhan region is characterized. All of the above allows us to make an assumption about the possibility of their use as a sorbent, as well as a base material for the creation of new sorption materials. The obtained results of the work can be used to remove toxicants from various media, minimize production costs, and increase the efficiency of adsorbents in the processes of their long-term operation.
Keywords: sorption processes; sorbents; mineral raw materials; removal of toxicants